2021
DOI: 10.3892/ijmm.2021.4942
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NFKBIZ affects bladder cancer progression via the PTEN/PI3K/Akt signaling pathway

Abstract: NF-κB inhibitor ζ (NFKBIZ), a member of the IκB family that interacts with NF-κB, has been reported to be an important regulator of inflammation, cell proliferation and survival. However, the role of NFKBIZ in bladder cancer (BC) remains unknown. The present study aimed to investigate the functions of NFKBIZ in BC. First, the expression levels of NFKBIZ and the associations between NFKBIZ expression and the clinical survival of patients were determined using BC tissue samples, BC cell lines and datasets from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Depending on the context, the IκBζ protein can promote or inhibit gene expression and the activation of signaling pathways involved in producing inflammatory molecules [ 110 , 112 ]. Several studies have suggested that NFKBIZ may be a driver gene for the development and progression of certain types of cancer, including lymphoma [ 110 , 113 ]. High IκBζ expression was explicitly detected in ABC DLBCL [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the context, the IκBζ protein can promote or inhibit gene expression and the activation of signaling pathways involved in producing inflammatory molecules [ 110 , 112 ]. Several studies have suggested that NFKBIZ may be a driver gene for the development and progression of certain types of cancer, including lymphoma [ 110 , 113 ]. High IκBζ expression was explicitly detected in ABC DLBCL [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mutation is thought to affect the interactions with nuclear factor-κB complexes that bind to that region, altering the transcriptional regulation of its target genes and leading to cancer predisposition (Esteban-Jurado et al 2015). Furthermore, NFKBIZ has been shown to be downregulated in bladder cancer and to affect the PI3K/AKT/mTOR pathway to inhibit proliferation (Xu et al 2021). To test if DLG2 influenced these pathways we investigated the phosphorylation levels of AKT, FOXO3 and S6 in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results from KEGG analysis indicated that MAPK, PI3K-Akt, and HIF-1 signaling pathways were markedly identified. MAPK and PI3K-Akt regulate tumor cell survival, proliferation, growth, mobility, and angiogenesis, whose activations were essential for BLCA metastasis and chemotherapy ( Xia et al, 2018 ; Sun et al, 2019 ; Lei et al, 2020 ; Ruan et al, 2020 ; Zhang et al, 2020 ; Xu et al, 2021a ; Kao et al, 2021 ). The HIF-1 signaling pathway was also discovered to be involved in hypoxic BLCA cell proliferation, migration, invasion, metastasis, and EMT, providing a rationale for clinical trials evaluating agents targeting this pathway ( Tickoo et al, 2011 ; Xue et al, 2014 ; Lu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%